Application of a photochemical model for the assessment of regional air quality in Southern Italy: procedures and results. (2017) - Tanzarella, Annalisa; Schipa, Ilenia; Morabito, Angela; Silibello, Camillo; Giua, Roberto; Assennato, Giorgio
A modelling system based on FARM chemical transport model is applied to assess the air quality (AQ) over the Apulia region (Southern Italy) for 2013. The most relevant pollutant sources in the region are a steel plant, the largest in Europe (in the Taranto area), a coal fired power plant, the second most powerful in Italy (in the Brindisi area) and biomass burning for residential heating. Simulation results indicate exceedances for PM10 daily limit value and benzo(a)pyrene (B(a)P) annual limit values occurring in some areas. The evaluation of the model performance has been conducted by using the software DELTA Tool, developed within FAIRMODE to support the application of the EU Air Quality Directive. Results show good performance of the model, with a tendency to underestimate PM10 and O3 levels. These results suggest the use of this modelling strategy for further source apportionment studies, in order to identify the sources that mainly affect air quality and to implement proper emission control strategies.